Detecting Fraudulent Financial Statement Using the Fraud Hexagon Model and ESG Disclosure as a Moderator - Maulana Ischaq; Imang Dapit Pamungkas (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The purpose of this study is to investigate the connection between the probability of financial statement fraud and the components of the Fraud Hexagon: pressure, opportunity, rationalization, capability, arrogance, and collusion. Additionally, we examine how Environmental, Social, and Governance (ESG) Disclosure functions as a moderator. Banks listed on the Indonesia Stock Exchange (IDX) between 2021 and 2024 are the subject of this study. We make use of secondary data gathered from business sustainability and annual reports. Purposive sampling was used to choose the bank sample depending on the completeness of the data. We use the Partial Least Squares (PLS) method of Structural Equation Modeling (SEM), which works well for evaluating models with complex variables, for the analysis. The results of this study are expected to provide insights into how each element of the Fraud Hexagon contributes to financial statement fraud and how ESG Disclosure can mitigate these risks.